Use of maps for planning research farms - Couper, D.C. (1996)
Topographic maps is the main type of maps used by farm managers. In agriculture, surveying is required to prepare topographical maps that indicate variations in the level of the land's surface. Topographical maps are the basis for farm planning. They can be used for determining slopes and land form. In combination with information on soil types, they can be used for farm planning.